Kombucha from Different Coconut Sugar Concentration as a Carbon Source - Merkuria Karyantina; Nanik Suhartatik (Jurnal Teknologi dan Industri Pangan, 2008)
Kombucha has been known as traditional medicine that can cure various diseases, such as hypercholesterol. Kombucha made of fermented sweetened tea using symbiotic growth of khamir and bacteria. Functional properties of kombucha related to metabolite that has been produced during fermentation process, glucuronic acid. The aim of this research was to get a fit carbon source that can produce kombucha which have highest glucuronic acid. The result showed that microbe that dominated at the beginning through the end of fermentation process was a group of khamir, i.e 1.81x107 ; 1.43x106 ; 2.40x107 ; 7.00x104 CFU/mL for 1, 4, 7, and 10% of additive coconut sugar. Kombucha at 4% of coconut sugar yielded 8.86 ppm of glucuronic acid. Meanwhile, kombucha with 10% of coconut sugar yielded 6.22 ppm of glucuronic acid. Total acid has no corelation with glucuronid acid formation during the fermentation process.Key words: kombucha, glucoronic acid, coconut sugar, anticholesterol